Tips for Religious Teachers When Implementing Religious Curriculum - Kurniatullaila; Albahri, Fauzan Putraga (Lembaga KITA, 2022)
This study was compiled based on library data and field research. In addition, many books related to the issues discussed are also used as primary and secondary reading material. All data are explored, categorized and analyzed using recursive and interpretive approaches to obtain a more complete understanding. The results of this paper show that tips for teachers in implementing a religious education curriculum in MIN Sabang can help students' parents and students by applying moral values, worship, and other religious precepts to their daily behavior. It shows that reaching out to Then make these values ​​a habit. The curriculum applied to the MIN Sabang is a competency-based curriculum that is designed to be a MIN education process that is conducive to the development of the potential of students. So that they are able to live independently as well as being able to live in the midst of a pluralistic society. The curriculum focuses more on competency targets than material mastery. The lack of quality teachers and the lack of supporting facilities are challenges faced by teachers in implementing the curriculum and because of this, religious teachers at MIN Sabang have not found effective tips as an effort to foster religious education at MIN Sabang.